(untitled) (World Bulletin of Social Sciences, 2025)
The evolution of information technologies has profoundly transformed modern healthcare systems. From electronic health records (EHRs) to telemedicine and AI-based diagnostics, information technologies (IT) now play a vital role in improving patient outcomes, reducing medical errors, and increasing healthcare efficiency. This paper explores the necessity of IT implementation in medicine, evaluates its current uses, and discusses its potential for addressing contemporary medical challenges.